Crystal Structure and Magnetic Properties of Zn doped Barium M-Hexaferrite - Nuraini, Umi; Amalia, Lita; Rosyidah, Kurniawati C.; Zainuri, Mochamad (Jurnal Fisika dan Aplikasinya, 2014)
Synthesis of Zn doped Barium M-Hexaferrite (BaFe12âˆ’xZnxO19) has been performed by coprecipitation method. The purified iron sand from Tulungagung is used as a precursor of Fe3O4. Synthesis of Zn doped Barium M-Hexaferrite with variations of x = 0.3, 0.5, and 0.7 has been calcined at temperatures of 1000Cfor 5 hours. Ion Zn2+ (with 0 x 0.7 wt %) does not change the crystal structure of Barium M-Hexaferrite (BaM), but give a slight displacement of the peak position of the diffraction pattern. SEMfigures showed that Zn doped Barium M-Hexaferrite have a hexagonal structure, similar to BaM structure. Doping of Zn has changed the magnetic properties of Barium M-Hexaferrit (BaM), from hard magnetic become soft magnetic. Barium M-Hexaferrit (BaM) has a value of Coercivity Field (Hc) and Remanence Magnetization (Mr) is 0.03734 T and 8.334 emu/g. At variation x = 0.3, the Remanence Magnetization (Mr) reaches the highest value. At this point, a value of Coercivity Field (Hc) and Remanence Magnetization (Mr) is 0.0506 T and 14.782 emu/gram respectively.